THE ROLE OF TOURISM IN ECONOMY - Jumayev Akbar Makhmudovich (European Science Publishing, 2024)
Tourism is distinguished by high investment multiplier. One sum included in the tourism industry will generate 4 sums in other industries. According to the World Tourism Organization, 11% of the world's gross national product, 10% of investments, 11% of world consumption and 5% of tax revenues account for tourism. We empirically test the relationship between tourism performance and multiple tourism dimensions, namely, tourism Attractions (A), Basics (B), and Context (C). We test the Tourism A-B-C model using data from regions of Uzbekistan. The results serve to state out major trends, which focus on further research on this topic globally, and also they might be useful in diversifying interventions to improve the impacts in the tourism industry advancement.
Keywords: Uzbekistan tourism, tourism infrastructure, tourism potential tourism performance, regional economic development, tourism A-B-C model.